Techniques and technologies for the breadmaking process with unrefined wheat flours. (May 2020) - Parenti, Ottavia; Guerrini, Lorenzo; Zanoni, Bruno
Abstract: Background: In recent years there has been an increasing interest in the production of wholegrain products owing to the positive effects shown on human health. Although refined flour still represents the standard reference in breadmaking technology, consumer demand for unrefined breads has grown greatly. The different chemical composition of unrefined wheat flours (UWFs), which includes specific fractions of milling by-products (i.e., wheat bran and wheat germ), favours the nutritional value, but it has a negative effect on technological performance. Therefore, it is useful to develop new strategies specifically designed to improve the quality of UWF breads. Scope and approach: The present review aims to set out the techniques and technologies that have been reported in the literature for the breadmaking process with UWFs, that is, from raw material processing to bread formulation and breadmaking methods. Key findings and conclusion: The evaluation of UWF quality is still based on the tests developed for refined flour, which cannot properly estimate UWF technological properties. The greatest efforts to improve the breadmaking performance of UWF have been focused on modifying the bread formula, mainly with the addition of improvers. Conversely, very little investigation has been carried out on adapting the breadmaking process to the different characteristics of the raw material. Overall, the use of UWF in breadmaking may require further investigations into processing strategies to improve the quality of the end product, hence increasing the consumption of healthy foods. Highlights: Positive effects on human health shown by the consumption of unrefined wheat products. Review of the use of unrefined wheat flours in the breadmaking process. Discussion of the standard criteria for the evaluation of unrefined bread quality. Description of modifications to the bread formula and process for unrefined flours. Proposal for new research to improve the employment of unrefined flours.